Linking Police and Hospital Road Accident Records: How Consistent Can It Be? - Marco Amorim (2014)
This paper presents the description of various steps to be applied in the linkage of road traffic accident records through a case study from the city of Porto, Portugal. The complexity of this process stems primarily from several issues found in the data sets: mistakes and missing values were frequently detected, and only a few common data fields could be matched by the linkage process. This study used the application of a mixed deterministic and weight-based probabilistic method to link police and hospital records. The tolerance calibration and weights computation were critical for the final linkage rate as well as for the correct matching of the results. The results obtained lay within the range of rates found by other authors. Furthermore, to improve the record linkage results, a validation process based on the emergency ambulance data was performed. Despite missing values, 98% of the matched records were verified as true matches. Finally, a preliminary investigation of bias after data linkage is described; it shows that the variables selected for comparison indicate similar statistical values. The main outcome of this study is a road accident linkage process that can be adapted, developed, and applied in different contexts and that aims to promote development of police, hospital, and emergency ambulance data in Portugal and other countries. Additional development is planned for each step presented in this paper.